The Discourse of Digital Transformation and the Epistemology of Islamic Education - Putri Adona; Junaidi Junaidi; Niimmasubhani Niimmasubhani; Devi Sospita (Prodi PAI STIT Sunan Giri Bima, 2026)
Digital transformation has triggered moral disruption, the fragmentation of religious authority, and the threat of misinformation within Islamic Education. This study aims to formulate a new paradigm through the reconstruction of an adaptive Islamic Education epistemology in the digital age. Employing a descriptive-qualitative literature review, this study adopts a multidisciplinary approach that integrates aspects of technology, sociology and the philosophy of religion. The findings reveal that the epistemological reconstruction of Islamic Education must synergise revelation, reason and analytical data through the strengthening of the tabayyun (verification) framework in the digital era, alongside the development of teacher competencies based on twenty-first-century skills. The implications of this study underscore the urgency of reformulating the Islamic Education curriculum so that it focuses not merely on the transfer of knowledge or the enhancement of students’ cognitive abilities, but is equally capable of preserving the authenticity of spiritual values and character. This model serves as a strategic reference for Islamic educational institutions in nurturing a generation that is technologically proficient whilst possessing profound moral character amidst the tide of global disruption.